1988
DOI: 10.1149/1.2095814
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Response of Zeolite‐Modified Electrodes

Abstract: As a prelude to using zeolites as supports for electrocatalysts, the voltammetric behavior of various analytes was examined at zeolite‐modified electrodes in aqueous solution. The following parameters were studied: preparation and characterization of electrodes, ability to concentrate or exclude analytes from dilute solution, linearity of response to concentration of analytes in solution, selectivity toward analytes of various sizes and charges, and the role of electrolyte cations in determining the response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
2
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(62 citation statements)
references
References 16 publications
8
51
2
1
Order By: Relevance
“…It can be seen from Figure 2 that the response current of ferricaferrous increases as the hydrated radius of the electrolyte co-ion decreases. This is in agreement with the literature [3,12]. The experimental results of Figure 2 indicate that the electroactive species existing in the zeolite are exchanged with the electrolyte co-ions, and then escape from the zeolite to be reduced on the interface of zeoliteelectrode-solution.…”
Section: Voltammetric Behavior Of Ferricaferrous At Fe 3 Yazcmesupporting
confidence: 92%
See 2 more Smart Citations
“…It can be seen from Figure 2 that the response current of ferricaferrous increases as the hydrated radius of the electrolyte co-ion decreases. This is in agreement with the literature [3,12]. The experimental results of Figure 2 indicate that the electroactive species existing in the zeolite are exchanged with the electrolyte co-ions, and then escape from the zeolite to be reduced on the interface of zeoliteelectrode-solution.…”
Section: Voltammetric Behavior Of Ferricaferrous At Fe 3 Yazcmesupporting
confidence: 92%
“…The voltammetric experiments illustrate that the optimum proportion of zeolite and graphite powder is 1 : 1. This conclusion was similar to that by Shaw [3]. From another discussion [27], it is known that the kind and concentration of the supporting electrolyte had obvious in¯uences on the electron transfer of ZME, so the effect of the supporting electrolytes was estimated in our experiment.…”
Section: Optimum Experimental Conditionssupporting
confidence: 88%
See 1 more Smart Citation
“…). According to previous reports, if electron transfer occurs between the species within the cavities of zeolite, peak intensity increases without any prominent shift in peak positions, termed an intra‐zeolite mechanism …”
Section: Resultsmentioning
confidence: 81%
“…A carbon paste electrode (CPE) modified with zeolite was tested for the determination of Cu(II) [5,6], a linear voltammetric response was obtained from 10\ to 10\ mol/l [5]. Ogorevc et al showed the latest use of a vermiculite modified CPE which exhibited a detection limit of 5;10\ mol/l Cu [7].…”
Section: Introductionmentioning
confidence: 99%